please answer.... i will mark you as brainliest
Attachments:
![](https://hi-static.z-dn.net/files/dd7/f78dd8915564275b5f2b6fc2aeb63053.jpg)
Answers
Answered by
2
LHS,
= cos theta / 1-sin theta + 1-sin theta / cos theta
= cos theta * cos theta + 1-sin theta * 1-sin theta / cos theta * 1-sin theta
= cos sq theta + 1+ sin sq theta -2sin theta / cos theta * 1-sin theta
= 2 -2sin theta / cos theta * 1-sin theta
=2(1-sin theta )/ cos theta * 1-sin theta
=2/cos theta
= 2 * 1/cos theta
=2 sec theta
LHS = RHS
Hence proved
Hope it helps..!!
Answered by
5
Answer:
refer to the above attachment for the solution
Attachments:
![](https://hi-static.z-dn.net/files/d04/afc06d0e442de456a620add327ac24ff.jpg)
Similar questions